Students’ Achievement in Writing Procedure text - Thomas Pandonge; Ika Paramitha Lantu; Vini Agneni Sangkuadje (Sintuwu Maroso Journal of English Teaching, 2023)
This research aims to describe the achievement of eighth-grade students in writing procedure text at SMP Negeri 3 Pamona Timur. This research is descriptive qualitative and the subject were eighth-grade students with a total number of 15 students. Data collection is done through tests. The researcher analyzes the data using a procedure task assessment rubric, researcher focuses on all aspects, namely: content, grammar, vocabulary, and mechanics. Based on the results of the research, it is obtained that the students achievement in writing Procedure text at SMP Negeri 3 Pamona Timur from all aspects is categorized into good criteria. The students’ writing achievement in the content aspect is 3.6 and it is categorized in good criteria. The students’ writing achievement in the organization aspect is 2,5 and it is categorized in fair criteria. The students achievement in the grammar aspect is 3,4 and it is categorized in good criteria. The students writing achievement in the vocabulary aspect is 2,8 and it is categorized fair criteria. The students’ writing achievement in the mechanics’ aspect is 2,2 and it is categorized in poor criteria